Hemodynamics in the cerebral circulation : numerical studies and experimental investigation - Chen, Liang (2008)
A nonlinear one-dimensional numerical model has been built up to study the cerebral blood flow in the circle of Willis (CoW). Three friction terms and two tube laws have been compared. A clinical-static autoregulation model obtained from the literature has been applied in the numerical model. Then the numerical model has been used to simulate hemodynamic changes in the CoW before and after clamping of internal carotid arteries (ICA) during carotid endarterectomy. The results show that the numerical model is a possible clinical tool in the estimation of hemodynamics in the patients. The interactive role of communicating arteries has also been studied. The results show that the diameters of anterior communicating artery and posterior communicating arteries together with the degree of stenoses of ICAs highly influence the cerebral hemodynamics.